Computing the Hosoya Polynomial of M-th Level Wheel and Its Subdivision Graph - Peng Xu; Muhammad Numan; Aamra Nawaz; Saad Ihsan Butt; Adnan Aslam; Asfand Fahad (Journal of Chemistry)
The determination of Hosoya polynomial is the latest scheme, and it provides an excellent and superior role in finding the Weiner and hyper-Wiener index. The application of Weiner index ranges from the introduction of the concept of information theoretic analogues of topological indices to the use as major tool in crystal and polymer studies. In this paper, we will compute the Hosoya polynomial for multiwheel graph and uniform subdivision of multiwheel graph. Furthermore, we will derive two well-known topological indices for the abovementioned graphs, first Weiner index, and second hyper-Wiener index.